Fuzzy Logic Application to Reduce Reactive Power on The 20 Kvdistribution Network of East Java APJ South Surabaya - Riswan Wahyudi (Institute of Computer Science (IOCS), 2021)
The voltage used on the distribution channel uses a 20 kV medium voltage which is controlled through a substation in the area. With the normal and reliable operation of the system which can maintain the continuity of the distribution of electrical energy is the hope of consumers as stakeholders of PT. PLN (Persero)DistribusiJawa Timur, Area Pelayanan Jaringan(APJ) Surabaya Selatan. The decline in the quality of electric power is a separate problem for the electricity provider and the customer side due to the complexity of the installed load. Technically, inductive loads with lagging power factor will absorb reactive power (var) on the load buses. To anticipate this, it is necessary to compensate for reactive power by using capacitor banks for various reasons including regulating power flow, improving system stability, correcting power factors, adjusting the voltage display and minimizing power losses. From the results of the power flow simulation (load flow) will be obtained the quantities of voltage and power losses which are input as a membership function required by the fuzzy logic method (fuzzy logic), the resulting output is the determination of the capacitor quantity based on the order of each loading bus on the distribution network.